E-Module Validation Based on Contextual Teaching and Learning for High School Optical Instruments - Ramadhanti, Revi Nur; Azhar, Azhar (Journal of Natural Science and Integration, 2022)
In this technological era, innovation is needed to improve the quality of education. Teachers are required to be able to integrate information and communication technology to produce teaching materials since the form of print media have gradually shifted to electronic media. The purpose of this research is to develop an e-module based on contextual teaching and learning which is valid for high school optical instruments. In this study, validation was carried out by 3 experts consisting of material experts, media experts and linguists. The data collection technique was carried out by providing a validation questionnaire in the form of a checklist. The data were analyzed using descriptive analysis by calculating the average of each indicator used to determine the validity of the developed e-module. The results of the study provide information that the e-module based on contextual teaching and learning on the material for optical high school instruments developed is valid with valid. The average score of the validation results obtained ranges from 3.00-4.00 so e-module belongs to valid. It means e-module has been successfully developed and it can be used in learning to enhance better teaching and learning process. Keywords: e-module, contextual teaching and learning, optical instruments, validation